Pola dan Narasi Gerakan Keislaman di Universitas Negeri Jakarta - Ahmad Hakam; Dewi Anggraeni; Abdul Fadhil (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2020)
This study aims to examine the patterns and narratives of the Islamic movement in Universitas Negeri Jakarta. The type of research is qualitative with a case study approach. The results of this study indicate that there are two types of Islamic movements in UNJ in the form of national and transnational movements. The pattern of the national Islamic movements in UNJ is represented by the academic activities organised through the PAI (Islamic Religious Education) study programme within the campus, and extra-campus MATAN organisation. Meanwhile, the transnational Islamic movements are represented by the Lembaga Dakwah Kampus (LDK) within the campus, and extra-campus organizations which include KAMMI, BMCI, and Nyantrend. The narrative of the Islamic movement promoted by the PAI (IRE) study programme through academic activities is Islamic moderation “more moderate more Indonesia,” MATAN as a national Islamic movement develops the narrative of Islamic Rahmatan Li al-’Alamin. LDK carries the slogan of Symuliatul Islam, KAMMI builds Islamic stories with Islam Shamil, BMCI Islamic narratives are preached with the slogan of Islam Kaffah, and Nyantred creates a narrative of Islam Ahlu Sunnah.